Surfactant-Assisted in situ Chemical Etching for the General Synthesis of ZnO Nanotubes Array - Wang Hongqiang; Li Ming; Jia Lichao; Li Liang; Wang Guozhong; Zhang Yunxia; Li Guanghai (Nanoscale Research Letters, 2010)
Abstract In this paper, a general low-cost and substrate-independent chemical etching strategy is demonstrated for the synthesis of ZnO nanotubes array. During the chemical etching, the nanotubes array inherits many features from the preformed nanorods array, such as the diameter, size distribution, and alignment. The preferential etching along c axis and the surfactant protection to the lateral surfaces are considered responsible for the formation of ZnO nanotubes. This surfactant-assisted chemical etching strategy is highly expected to advance the research in the ZnO nanotube-based technology.